2015
DOI: 10.1097/sla.0000000000001421
|View full text |Cite
|
Sign up to set email alerts
|

FAST Ultrasound Examination as a Predictor of Outcomes After Resuscitative Thoracotomy

Abstract: With a high degree of sensitivity for the detection of potential survivors after traumatic arrest, FAST represents an effective method of separating those that do not warrant the risk and resource burden of RT from those who may survive. The likelihood of survival if pericardial fluid and cardiac motion were both absent was zero.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Perhaps ultrasound may aid a better identification of potential survivors, as a recent study showed that the absence of both cardiac motility and pericardial effusion on transthoracic ultrasound is associated with zero survivors 13 . On the other side, precious time may be lost while performing ultrasound which may even affect neurological outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps ultrasound may aid a better identification of potential survivors, as a recent study showed that the absence of both cardiac motility and pericardial effusion on transthoracic ultrasound is associated with zero survivors 13 . On the other side, precious time may be lost while performing ultrasound which may even affect neurological outcome.…”
Section: Discussionmentioning
confidence: 99%
“… 15 17 18 Initial utilization of the focused assessment with sonography for trauma (FAST) may potentially avoid this futile intervention as the absence of cardiac motion or pericardial effusion on a FAST examination results in a zero survival rate. 19 Although it may be able to identify patients with a survival potential, it does not necessarily predict survival in those ultimately undergoing ERT. Nonetheless, clinicians perform this procedure in an effort to expertly weigh the last chance of survival against the risk of rescuing patients with anoxic brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, resuscitative thoracotomies convey a measurable risk to physician staff performing the procedure 12 . Previous work has been done on attempts to identify patients with higher chances of survival including point‐of‐care ultrasound; however, a persistent limitation in the care of these patients is the lack of reliable total downtime 13 . Our data suggest that the use of the novel app that is currently available can almost always provide further details surrounding a traumatic arrest.…”
Section: Discussionmentioning
confidence: 90%